Sustentación de caso: propuesta de un plan estratégico del ingreso al mercado peruano de una empresa del sector fast fashion - Berckholtz Molfino, César Sebastián (2018)
The main objective of this work is to do a integral business analysis of the Fast Retailing Group (FR), in order to determine the viability of entering to the Peruvian market in 2019, in order to consolidate its growth and meet its objective of become the first textile company in the world. On this way, this Work has been divided into four chapters; the first, focused in performing the internal and external strategic diagnosis; the second, in the formulation of a strategy; the third in the methodology to implement the proposed strategy; and the fourth in the establishment of strategic controls that monitor the implement of the strategy. After the analysis, it has been set that the FR Group is a company that asumes all his business process and trade with a short group of providers in the network, allowing the group to make good quality products with a low cost, generating a greater margin allowing to make his investment more profitable. In this regard, and in order to consolidate its entry into the Peruvian market, considering its potential, it has been proposed to the Group to establish a subsidiary in Lima of its best brand, UNIQLO, together with its brands PLST and GU, implementing a transnational strategy that allow them to continue with their objective of differentiation and at the same time to generate greater acceptance in the country, all of that combined with a strategy of vertical integration forward, which will allow them to reduce the value of their operating costs. In the same way, before entering to the Peruvian market and in order to create expectations, it has been proposed to create strategic alliances with bloggers and influencers to promote the brand as well as with different ONGs that allows to development social projects, generating bigger attention and interest on the consumers. Finally, it has been suggested to invest and enhancement of its online sales pages, since this is a low cost, high profitability sales channel that is gaining ground in the market, taking advantage of the fact that currently the vast majority of retail stores in the Peru does not have this tool implemented efficiently.